A systematic literature review for smart hydroponic system - Muhasin, Haifaa Jassim; Gheni, Ali Yahya; Ismarau Tajuddin, Nur Ilyana; Izni, Nor Aziyatul; Yah Jusoh, Yusmadi; Azhar Aziz, Khairi (Bulletin of Electrical Engineering and Informatics, 2024)
Hydroponics is the cultivation of plants by utilizing water without using soil which emphasizes the fulfillment of the nutritional needs of plants. This research has introduced smart hydroponic system that enables regular monitoring of every aspect to maintain the pH values, water, temperature, and soil. Nevertheless, there is a lack of knowledge that can systematically represent the current research. The proposed study suggests a systematic literature review of smart hydroponics system to overcome this limitation. This systematic literature review will assist practitioners draw on existing literature and propose new solutions based on available knowledge in the smart hydroponic system. The outcomes of this paper can assist future researchers by providing a guideline for user in highlighting approaches for the successful implementation of smart hydroponic system.